Sarcoidosis : a clinician's guide - Baughman, Robert P.; Valeyre, Dominique (Elsevier, 2018)
Get a quick, expert overview of the etiology, diagnosis, and management of pulmonary and extra pulmonary sarcoidosis with this concise, practical resource. Drs. Robert B. Baughman and Dominique Valeyre fully cover the recent advances in various aspects of this disease, including new genetic studies and new diagnostic techniques. It's an ideal resource for pulmonologists and respiratory medicine specialists, as well as primary care physicians and pulmonary/respiratory care nurses. --